Optimization of the reaction parameters of heavy naphtha reforming process using Pt-Re/Al2O3 catalyst system - Hussien A. Elsayed; Mohamed F. Menoufy; Seham A. Shaban; Hoda S. Ahmed; Bassem H. Heakal (Egyptian Journal of Petroleum)
One of the most significant procedures in oil refineries is naphtha catalytic reforming unit in which high octane gasoline is gained. Normally, in oil refineries, flow instability in the composition of feedstock can affect the product quality. The aim of the present work was focused on modifications of the final product flow rate and product’s octane number with respect to the modifications of the feedstock composition. The main three reforming reactions investigated, namely; dehydrogenation, dehydrocyclization, and hydrocracking were conducted employing silica supported bimetallic (Pt-Re) patented catalyst. Optimization of the catalytic process reaction conditions, i.e.; temperature, hydrogen pressure and liquid hourly space velocity (LHSV) was carried out with regard to conversion and selectivity. The optimization results indicated that heavy naphtha component conversion (paraffin’s and naphthenes) increases with an increasing in reaction temperature and pressure while decreases with an increase in LHSV. The kinetic study of catalytic reforming reactions reported helped establishing the reaction model explicitly.